2018
DOI: 10.1016/j.atherosclerosis.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Soluble endoglin and hypercholesterolemia aggravate endothelial and vessel wall dysfunction in mouse aorta

Abstract: The results indicate that long-term hypercholesterolemia combined with high levels of sEng leads to the aggravation of endothelial and vessel wall dysfunction in aorta, with possible alterations of the membrane endoglin/eNOS signaling, suggesting that high levels of soluble endoglin might be considered as a risk factor of cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 36 publications
7
31
0
1
Order By: Relevance
“…In fact, it has been reported that sEng contributes to endothelial dysfunction. Thus, sEng synergizes with hypercholesterolemia to aggravate endothelial and vessel wall dysfunction in vivo [43,45] and shows pro-inflammatory activity via nuclear factor-kappa B (NFkB) and interleukin 6 (IL6) in human endothelial cells in vitro [78]. Furthermore, exosomes from preeclamptic women induced vascular dysfunction by delivering sEng to endothelial cells [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been reported that sEng contributes to endothelial dysfunction. Thus, sEng synergizes with hypercholesterolemia to aggravate endothelial and vessel wall dysfunction in vivo [43,45] and shows pro-inflammatory activity via nuclear factor-kappa B (NFkB) and interleukin 6 (IL6) in human endothelial cells in vitro [78]. Furthermore, exosomes from preeclamptic women induced vascular dysfunction by delivering sEng to endothelial cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…If left untreated, preeclampsia can lead to serious, even fatal, complications for both mother and baby [41,42]. Noteworthy, several lines of evidence support a pathogenic role of sEng in cardiovascular conditions and diseases, including hypertension, endothelial dysfunction, anti-angiogenic activity, increased vascular permeability, vascular remodeling, and inflammation-associated leukocyte adhesion and transmigration [14,15,33,34,[42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, elucidating novel mechanisms of MΦ polarization may lead to a better understanding of their roles in vascular inflammation. In this manuscript, we report a new link between pro-inflammatory GM-MΦ and endothelial cells, by which GM-MΦ-derived MMP-12 targets membrane bound endothelial endoglin, leading to the release of sEng, a soluble protein with pro-inflammatory properties and the potential to promote endothelial dysfunction in combination with hypercholesterolemia [55]. Our results suggest that there is a direct and synergic effect of both MMP-12 and sEng in the context of the GM-MΦ/pro-inflammatory macrophage response (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Shedding of the ectodomain of endoglin can be triggered by inflammation, tumor necrosis factor α (TNF-α), endothelial injury, or anti-endoglin antibodies [47,48,49,50,51]. Of note, sEng (i) displays pro-inflammatory activity via nuclear factor-kappa B (NFκB) and interleukin 6 (IL6) in human endothelial cells [52]; (ii) shows antiangiogenic activity and increased vascular permeability in vitro and in vivo [40,51,53]; (iii) modulates inflammation-associated monocyte adhesion and transmigration [13]; (iv) contributes to endothelial dysfunction, as shown in transgenic animals overexpressing human sEng [54,55]; and (v) regulates vascular development and arteriovenous malformations by modulating angiogenesis [47]. Therefore, identification of the mechanisms responsible for the generation of sEng in the inflammatory context may provide novel therapeutic targets for inflammation-related vascular pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that sEng levels increased both the expression of cell adhesion molecules and the number of rolling leukocytes, and that they impaired endothelial-dependent vascular function [ 116 ]. Moreover, sEng levels were higher in blood during endothelial injury or inflammation, but also in other vascular pathological conditions, such as atherosclerosis, hypercholesterolemia, hypertension, and T2D [ 117 ]. A clinical study conducted on 288 patients with T2D, hypertension, and healthy controls showed a significant correlation between endoglin and glycemia, glycated hemoglobin, systolic blood pressure, left ventricular hypertrophy and endothelial dysfunction [ 118 ].…”
Section: Oxidative Stress and Cellular Biomarkers For Prevention Amentioning
confidence: 99%